Legal Politics of Overcoming the Crime of Money Laundering in Equitable Law Enforcement - Gusri Putra Dodi; Helmi; Hafrida (PT FORMOSA CENDEKIA GLOBAL, 2024)
In simple terms, money laundering is an effort made to disguise or make unclear hot or dirty money (dirty money), namely money originating from illegal practices such as corruption, trafficking of women and children, terrorism, bribery, smuggling, selling illegal drugs, gambling, prostitution, banking crimes and other unhealthy practices. The term Money Laundering (ML) denotes the process carried out by criminals to encourage the true origin of the proceeds obtained from criminal activities and to make their money appear to be clean money or legitimate income. A good law must be able to become a social engineering tool that is able to create or change a bad or unfavorable situation to a better one, so that society will increasingly feel the benefits of the law. So what is meant by the term law is a tool of social engineering is not just a theory as written by Roscoe Pound. If you want to pay special attention to the development of law in Indonesia, you can also see it from the laws created by the government. The development of this legislation can be seen from 3 (three) government periodizations, namely: old order government, new order government, and post-reformation government. One of the regulations that has generated a lot of content and controversy in the regulation of the eradication and prevention of money laundering crimes is the provisions of Article 69 of Law no. 8 of 2010. As for Article 69 of Law no. 8 of 2010 states